The Impact of Fiscal Policy on the Economic Growth of OECD Members Between 1985 and 2015 - Afonso, Oscar; Alves, Paulo; Fortuna, Natércia (Panoeconomicus, 2024)
We aim to evaluate the impact of fiscal policy on the OECD countries’ economies between 1985 and 2015. We estimate the impact of fiscal policy using econometric estimation based on panel data. We conclude that government spending on primary expenses and government spending on military are fiscal policies that negatively impact economic growth. In turn, government spending on education and tax revenue have a positive effect on economic growth. JEL: C23, E62, F43.